METHODOLOGY FOR DIAGNOSING THE MASTERING OF PRIMARY GRADE STUDENTS' SKILLS FOR ACTIVITY - Dilorom Mukimovna Tashpulatova; Sevinch Toshpolatova (Web of Journals Publishing, 2024)
The article discusses the practice-oriented methods of diagnosing the mastering of primary school students' skills for mastering knowledge, mastering the foundations of education, and diagnosing their skills for preparing for practical activity.
Keywords: Primary school, student mastering, diagnostic methodology, knowledge and skills, educational readiness, educational readiness and practical readiness, practice.